Physical Activity and urinary Incontinence in Older Adults: A community-Based Study - Lee, Andy; Hirayama, F. (Bentham Science Publishers, 2012)
Background: Urinary incontinence (UI) is a distressing condition that affects the lifestyle of older people. To investigate the relationship between UI and physical activity among older adults, a community-based study was conducted in Japan. Methods: A total of 700 men and 300 women (mean age 66.2, SD 7.7 years) were recruited from the community in middle and southern Japan. The International Consultation on Incontinence Questionnaire-Short Form was administered by face-to-face interviews to ascertain UI status. Habitual physical activity levels (walking, moderate and vigorous activities) were assessed using the International Physical Activity Questionnaire and measured in terms of energy expenditure as metabolic equivalent tasks (MET). Results: The prevalence of UI was 7.2% (n = 49) among the 683 eligible male participants and 27.5% (n = 82) among the 298 female participants, who had experienced urine leakage for 2.6 (SD 1.9) years and 4.2 (SD 5.1) years, respectively. Habitual walking levels were lower among incontinent subjects than others without the condition. The adjusted risk of UI was 0.36 (95% confidence interval (CI) 0.14, 0.92) for men and 0.43 (95% CI 0.20, 0.96) for women, when comparing frequent walkers with over 1000 MET minutes of walking per week to completely sedentary participants. The prevalence of UI also decreased with total and moderate activity levels, but the corresponding reductions in risk were not statistically significant. Conclusion: The finding of an inverse association between UI and walking has important implications for the prevention and treatment of this distressing condition.